Evaluation of Nutrient Digestibility and Metabolizable Energy of Yeast-Fermented Acacia mangium Leaf by Japanese Quails - Saichon Lerdsuwan; Duangjai Pisuttharachai; Warrapong Nalinanon (My University, 2023)
The nutrient digestibility and the metabolizable energy (AME) of Acacia mangium leaf (AM) and yeast-fermented AM (YFAM) by Japanese quails were investigated. Fifty-four of 4-weeks-old Japanese quails were divided into 3 groups with six replications of three quails. Each quail was randomly fed with an experimental diet composed of dextrose (protein-free diet for determining endogenous excretion) 40 % AM and 40% YFAM. The quails were raised individually in a metabolic cage, where feed and water were provided ad-libitum. Both feed intake and feces weight were recorded. Experimental diets and excreta were sampled and subjected to proximate analysis for gross energy. The results of nutrient composition indicated that the fermentation AM with yeast highly significantly increased (P<0.01) dry matter (DM), ash, and nitrogen-free extractives (NFE) content but decreased (P<0.01) crude protein (CP), crude fiber (CF), and gross energy (GE) content. In addition, the birds fed dietary YFAM compared with AM showed significantly increased (P≤0.01) DM, organic matter (OM), CP, and GE digestibility but decreased (P≤0.01) EE and CF digestibility. The protein utilization of birds fed dietary YFAM showed significantly greater (P≤0.01) FI, protein retained, protein intake, net protein utilization (NPU), and AME than those fed dietary AM. In conclusion, the fermentation of AMLM with yeast improved nutrient composition and enhanced the digestibility of nutrients, protein utilization, and AME of AMLM in Japanese quail.
Keywords: Acacia mangium; Animal Nutrition and Physiology